Penyuluhan dan Pendampingan kepada Guru dan Siswa MDTA Tentang Arif dan Bijak dalam Penggunaan Smartphone - Khomarudin, Agus Nur; Novita, Rina; Darmawati, Gusnita (Jurnal Dedikasia : Jurnal Pengabdian Masyarakat, 2023)
Since the Covid-19 pandemic broke out, the presence of smartphones is felt to be very important, especially for students. The presence of a smartphone in the family must be addressed wisely and prudently. Because in essence, a smartphone is a technology that is analogous to a knife with 2 sides. Smartphones can have a positive impact if used in a positive direction and vice versa, they will cut and self-destruct if used in a negative direction. Awareness of the negative impact of smartphone use in early childhood should be a concern for parents because it can reduce the healthy quality and social life of adolescents. Early childhood is the next generation for religion, homeland, and nation which must be formed with the basic provisions of character so that they grow and develop into pious children who are assets for both parents. The target of this PkM activity is to provide counseling to teachers and students of MDTA Al-Mukminun Biaro, Kab. Religion. To find out the level of effectiveness of this PkM activity, an assessment was carried out using the media questionnaire instrument. Based on the processing of the questionnaire, the result was that this PkM activity obtained an average score of 82.71% in the good category. Even though this activity has obtained good results based on the assessment of the MDTA teachers, consistent efforts are needed and an increase in the effectiveness of PkM implementation for the next period. Efforts to increase the effectiveness of PkM implementation are also based on several suggestions and input submitted by MDTA teachers through effectiveness questionnaires.